Biodiversity and characterization of Staphylococcus species isolated from a small manufacturing dairy plant in Portugal - Soares, José C.; Marques, M. Rosário; Tavaria, Freni K.; Pereira, Joana O.; Malcata, F. Xavier; Pintado, Manuela M. (International journal of food microbiology, 2011)
The level and the diversity of the staphylococcal community occurring in the environment and dairy products of a small manufacturing dairy plant were investigated. Species identification was performed using different molecular methods, viz. Multiplex-PCR, amplified ribosomal DNA restriction analysis (ARDRA), and sodA gene sequencing. The main species encountered corresponded to Staphylococcus equorum (41 isolates, 39.0%), S. saprophyticus (28 isolates, 26.7%) and S. epidermidis (15 isolates, 14.3%). Additionally, low incidence of enterotoxin genes was obtained, with only 9 strains (8.6%) being positive for one or more toxin genes. With regard to antimicrobial resistance, 57.1% of the isolates showed at least resistance against one antibiotic, and 28.6% were multi-resistant, which might accomplish resistance for up to 6 antibiotics simultaneously. These results provided evidence that the presence of Staphylococcus species in dairy environment are mostly represented by S. equorum and S. saprophyticus, and illustrate that carrying antimicrobial resistance genes has become reasonably widespread in cheese and dairy environment. ► High diversity of Staphylococcus species isolated from a cheese dairy plant. ► Predominance of S. equorum and S. saprophyticus species. ► A considerable fraction of staphylococci presents antimicrobial resistance genes. ► Low incidence of enterotoxin genes was obtained.